Persuasion a key idea for business and society - Dunne, Stephen 1982- (Key ideas in business and management, 2025)
Persuasion. Philosophers have worried about it. Political and economic actors have weaponised it. Psychologists have measured it. Prose writers have required it. We're all subjected to it. And some have even mastered it. Of them, we are often very suspicious. Why is that? Persuasion: A Key Idea for Business and Society asks the disciplines of philosophy, politics, psychology, and prose analysis - the 4 Ps of persuasion - to answer this important question.The book is written for students and teachers of business and marketing but will also guide researchers across the social sciences and humanities.